Decriminalising voluntary active euthanasia through the recognition of fundamental human rights : a comparison of South Africa and foreign jurisdictions - Carstens, Pieter Albert, 1960- (University of Pretoria, 2022)
Dissertation (LLM (Public Law))--University of Pretoria, 2021.